Enhanced Recovery after Surgery Applied to Pediatric Laparoscopic Cholecystectomy for Simple Cholelithiasis: Feasibility and Teaching Insights - Luca Pio; Berenice Tulelli; Liza Ali; Lucas Carvalho; Marc Chalhoub; Florence Julien-Marsollier; Arnaud Bonnard (MDPI AG, 2023)
Background: Same-day discharge after a cholecystectomy is a common practice in the adult population and has been demonstrated as safe and viable for children as well. However, there is a lack of comprehensive teaching models for pediatric cholecystectomy. Drawing inspiration from standardized outpatient procedures, this study aimed to assess the clinical outcomes and feasibility of teaching programs and an Enhanced Recovery After Surgery (ERAS) protocol following ambulatory laparoscopic cholecystectomy in pediatric patients. Methods: In 2015, an ERAS pathway for laparoscopic cholecystectomy (LC) was implemented, focusing on admission procedures, surgery timing, anesthetic choices, analgesia, postoperative feeding, mobilization, and pain assessment. Day-case surgery was not applicable for acute cholecystitis, choledochal lithiasis, sickle cell disease, and hereditary spherocytosis cases. The protocol was employed for a group of attending surgeons and fellows, as well as a group of residents under the supervision of experienced surgeons. A retrospective analysis was conducted to evaluate the feasibility and effectiveness of ambulatory cholecystectomy in children and its utilization in training pediatric surgical trainees. Results: Between 2015 and 2020, a total of 33 patients were included from a cohort of 162 children who underwent LC, with 15 children operated on by senior surgeons and 18 by young surgeons. The primary diagnoses were symptomatic gallbladder lithiasis (n = 32) and biliary dyskinesia (n = 1). The median age at the time of surgery was 11.3 years (interquartile range (IQR) 4.9-18), and the median duration of surgery was 54 min (IQR 13-145). One intraoperative complication occurred, involving gallbladder rupture and the dissemination of lithiasis into the peritoneal cavity. Three patients (9%) required an overnight stay, while no postoperative complications or readmissions within 30 days were observed. ERAS was successfully implemented in 30 patients (91%). No significant differences in surgical outcomes were noted between senior and young surgeons. At an average follow-up of 55 months, no long-term sequelae were identified. Conclusions: These findings align with the current trend of increasing use of outpatient laparoscopic cholecystectomy and underscore its feasibility in the pediatric population. The application of a structured ERAS protocol appears viable and practical for training the next generation of pediatric surgeons. Level of Evidence: Level III.